Dhruva Advisors : culture as north star of growth - Sharma, Sunil (Professor of business policy), (SAGE Business Cases., 2019)
Dhruva was founded by Dinesh Kanabar, ex-Deputy CEO of KPMG. Dinesh and other founding Partners had worked with the Big-4 firms. They had an aspiration to build a distinctive professional service firm (PSF) in the tax advisory space. Over the next four years, the firm grew rapidly by following principles of Partner stewardship, high-end client work, and cooperative work-culture. New Partners were added only to bridge capability gaps and not just for increasing topline. There was no active client solicitation and the firm stuck to policy of complex client work and premium pricing. The founding team was very particular that the organizational culture was participative, transparent and egalitarian. Though the firm had established itself as a reputed tax advisory firm, the journey so far was guided more by Partners' convictions and beliefs. The next phase of growth would be a true test of how the alternate paradigm could be scaled.